On partial derivatives of the i-function of r-variables - (:unkn) unknown (Azerbaijan Mathematical Society, 2020)
The object of this paper is to establish some formulas involving the partial derivatives of the Prasad’s I-function of r-variables. On specializing the parameters, the results can be reduced to derivatives of H-function of r-variables, H-function of two variables. As a result, we have four corollaries concerning the multivariable H-function. © 2010 AZJM All rights reserved.
Keywords: I-function of two and several complex variables; Multivariable H-functions; Partial differentiation